Drying characteristics of non-centrifugal sugar. Issue 16 (16th November 2020) - Verma, Pankaj; Shah, Narendra; Mahajani, Sanjay
Abstract: Non-centrifugal sugar (NCS), generally known in most parts of Asia as jaggery, is a commonly used sweetener in food preparations. Sun drying of NCS has been reported to improve its shelf life. However, there is no systematic study, supported by relevant data and analysis, for this claim. In this article, the influence of temperature and relative humidity (RH) of the medium on the drying rate of jaggery is studied. The optimum drying temperature and humidity for jaggery of different compositions are determined. Jaggery containing low levels of reducing sugars (RSs) (2–5%) has lower equilibrium moisture content (EMC). For this reason, moisture could be reduced to as low as 0.5% within 250 minutes. Case-hardening is realized for the product with low RS content (typically ≤ 6%), and it does not allow one to employ high temperatures for drying. For jaggery containing high RS (10–15%), case-hardening was not evident, while the higher EMC does not permit moisture reduction below 4–5% under otherwise similar conditions.